A Physical Model to Assess Landslide Susceptibility on Large Areas: Recent Developments and Next Improvements. (2016) - Passalacqua, Roberto; Bovolenta, Rossella; Federici, Bianca; Balestrero, Dario
Abstract: The Authors have developed and refined, along the past years, a physically-based Integrated Hydrological-Geotechnical model (IHG), which is able to assess the territorial landslide susceptibility per effect of rain histories. The IHG model has been applied on two benchmark sites in Liguria, showing its reliability. Hence, it may become a very useful instrument in order to allow proper risk evaluations and/or land use-planning over wide areas, especially taking into account its forecasting ability if using short/medium term meteorological predictions. Along the paper the last application of the IHG model, its improvements and the next developments are thoroughly described.